التحديد الاستقطابي لعنصري الكادميوم والرصاص في الشعر كمؤشر صحي - ناصر, هاجر; مرستاني, زكريا; خيربك, رزان (Latakia University Journal -Basic Sciences Series, 2018)
تمَّ في هذه الدراسة تحديد مستويات الكادميوم والرصاص في شعر المتبرعين المرضى والأصحاء. جمعنا عينات الشعر وقمنا بتحليلها بوساطة الطريقة الاستقطابية لمعرفة محتوى نزر عنصري الكادميوم والرصاص في عينات الشعر. وجد أن محتوى الرصاص والكادميوم في الشعر كان مرتفعاً بشكل ملحوظ عند المتبرعين المرضى (38.2 µg/g – 19.7 µg/g) بالنسبة إلى الرصاص، (2.1 µg/g – 0.4 µg/g) بالنسبة إلى الكادميوم. بينما كان التركيز منخفضاً عند المتبرعين الأصحاء(8.8 µg/g – 7.8 µg/g) بالنسبة إلى الرصاص، (0.3 µg/g – 0.2µg/g) بالنسبة إلى الكادميوم. وقد تبين في هذه الدراسة ارتباطاً بين تراكيز العناصر في الشعر وصحة الجسم، واستنتجنا أن الشعر مؤشر جيد لتقدير محتوى الكادميوم والرصاص في الجسم وعلاقته بالأمراض، وأن الطريقة الاستقطابية قابلة للتطبيق في التحاليل المخبرية والمراقبة الطبية. Cadmium and Lead level were examined in hair of patients and healthy donors. Hair sample were collected and analyzed for their contents of the trace metals (Cd, Pb) by Voltammetry. It was found that the existence of Cadmium and Lead in the hair was significantly higher in the patients (19.7 µg/g – 38.2 µg/g) for lead, (0.4 µg/g – 2.1 µg/g) for cadmium. On the other hand, the healthy had lower concentration (7.8 µg/g – 8.8 µg/g) for Lead, (0.2 µg/g – 0.3µg/g) for cadmium. In this study, hairs were analyzed to find the effect these elements on health. Correlation coefficients between the levels of the elements in hair found in this study showed that hair is a good indicator of Cadmium and Lead in the hair. The method is applicable as a tool for monitoring pollution level of groups.